Pengaruh Hasil Belajar Matematika terhadap Hasil Belajar Akuntansi pada Mahasiswa Jurusan Akuntansi Politeknik Negeri Banjarmasin. - Priyougie; Ahsanul Haq; Linda Permanasari (Indonesian Journal of Applied Accounting and Finance, 2021)
There are several similarities between mathematics and accounting, which both emphasize the use of logic, use symbols, and have definite formulas. In general, if a student has good math skills, chances are that his accounting skills are also good. Therefore, the researcher wanted to know whether there was an effect of mathematics learning outcomes on accounting learning outcomes for students of the Accounting Department at the Banjarmasin State Polytechnic. For testing the hypothesis, the researchers took the final grade data for mathematics courses in the first semester and the average final grade data from several accounting-based courses in the following semesters such as Intermediate Financial Accounting, Cost Accounting, Accounting Information Systems, Public Sector Accounting. , and Introduction to Accounting Practices. After the data is tested for normality, a correlation coefficient test, a coefficient of determination test, and a simple linear regression test were conducted. The test results indicate that there is a strong influence between the learning outcomes of mathematics courses on the learning outcomes of several accounting courses for students of the Accounting Department of the Banjarmasin State Polytechnic. The average learning outcomes of several accounting courses are influenced by 47.66% by learning outcomes of mathematics courses while the remaining 52.34% is influenced by other variables.